Percutaneous left atrial appendage occlusion – treatment outcomes and 6 months of follow-up – a single-center experience - Karczewski, Michał; Woźniak, Sebastian; Skowronek, Radomir; Burysz, Marian; Fischer, Marcin; Anisimowicz, Lech; Demkow, Marcin; Konka, Marek; Ogorzeja, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Aim : To present the results of treatment and evaluate 6 months of follow-up in a group of patients with non-valvular atrial fibrillation, who underwent the procedure of percutaneous left atrial appendage occlusion (PLAAO). Material and methods: Percutaneous left atrial appendage occlusion was performed in 34 patients with non-valvular atrial fibrillation and contraindications for oral anticoagulation therapy. The risk of thromboembolic and bleeding complications was determined based on the CHA2DS2VASc and HAS-BLED scales. The Amplatzer Amulet system from St. Jude Medical was used. On the first postoperative day, all patients were started on double antiplatelet therapy with 75 mg/day of acetylsalicylic acid (ASA) and 75 mg/day of clopidogrel (CLO). On the 30th postoperative day, the efficacy of the antiplatelet therapy was assessed with impedance aggregometry using a Multiplate analyzer (Roche). Echocardiographic examinations were performed intraoperatively and on the first postoperative day; subsequently, follow-up examinations were conducted 1 and 6 months after the implantation. Results: In all patients, proper occluder position was observed throughout the follow-up. No leakage or thrombi around the implants were found. No strokes or bleeding complications associated with the antiplatelet therapy were observed. Multiplate assessment of platelet activity was conducted in 20 out of 34 patients. The efficacy of ASA treatment was demonstrated in all patients; no response to clopidogrel treatment was observed in 5 out of 20 patients. One patient suffered from cardiac tamponade, which required the performance of full sternotomy. Local complications (hematomas of the inguinal region) were observed in 3 patients. One of the patients died for reasons unrelated to the procedure. Conclusions: Percutaneous left atrial appendage occlusion is an effective procedure in patients with non-valvular atrial fibrillation and contraindications for chronic anticoagulation therapy. Further observation is necessary to evaluate the long-term results.